Silencing race : disentangling blackness, colonialism, and national identities in Puerto Rico - Rodríguez-Silva, Ileana M., 1970- (Palgrave Macmillan, 2012)
In their quest for greater political participation within shifting imperial fields--from Spanish (1850s-1898) to US rule (1898- ) Puerto Ricans struggled to shape and contain conversations about race. In so doing, they crafted, negotiated, and imposed on others multiple forms of silences while reproducing the idea of a unified, racially mixed, harmonious nation. Hence, both upper and working classes participated, although with different agendas, in the construction of a wide array of silences that together have prevented serious debate about racialized domination. This book explores the ongoing, constant racialization of Puerto Rican workers to explore the 'class-making' of race.